The influence of spirituality and physical activity level on responsible behaviour and mountaineering satisfaction on Mount Kinabalu, Borneo - Esfahani, M.; Musa, G.; Khoo, S. (Taylor & Francis, 2014)
Psychological and physical conditions may influence the behaviour and satisfaction of mountaineers. This exploratory study aims to investigate the influence of spirituality and physical activity level on responsible behaviour and mountaineering satisfaction among mountaineers on Mount Kinabalu, Borneo. We surveyed all mountaineers at the base of Mount Kinabalu after the completion of their climb over a period of one month in 2013. A total of 916 mountaineers completed the questionnaires and we analysed the data using structural equation modelling. The findings indicated that spirituality positively influences both responsible mountaineering behaviour and satisfaction. A high physical activity level moderates both of these relationships. The study contributes to knowledge on the important roles of and physical activity level in influencing both responsible behaviour and satisfaction among mountaineers. It also provides theoretical, marketing and managerial contributions.